-12=4f+6f

Simple and best practice solution for -12=4f+6f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=4f+6f equation:



-12=4f+6f
We move all terms to the left:
-12-(4f+6f)=0
We add all the numbers together, and all the variables
-(+10f)-12=0
We get rid of parentheses
-10f-12=0
We move all terms containing f to the left, all other terms to the right
-10f=12
f=12/-10
f=-1+1/5

See similar equations:

| x-4=2x-18` | | 3(l-6=15 | | 5/2x+1/2x=17.5+7/2x | | 90+z+130=180 | | 2y+1=y-5. | | -4=s-4 | | -4a+3+5a=11-25 | | m=234 | | −2=−4+t | | 11x+5=7x+41 | | 5+8=-13-2x | | 2x+6+135+25=180 | | 5/2k+8-11/2k=5k-4 | | 5=4-b | | 2m+2m=12 | | -21=-18x+33 | | 4x-8=5x+30 | | 38=3p+5 | | 5w=10=100 | | 16=2x+1-7 | | X^+2-3x+8=0 | | 28t^2-17t=0 | | 5=x+5,x=10 | | 2(v+16)=40 | | 9-2x-6x=62 | | 11x-17=65=180 | | 32x+5=44x-9 | | 8w−8=80 | | f/4-5=-5 | | 3.2x+11=1.2x-1 | | -14=23r−14=23 | | 6÷y=2 |

Equations solver categories